2003
DOI: 10.1176/appi.ajp.160.2.255
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate in the Treatment of Binge Eating Disorder Associated With Obesity: A Randomized, Placebo-Controlled Trial

Abstract: Topiramate was efficacious and relatively well tolerated in the short-term treatment of binge eating disorder associated with obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
246
0
10

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 437 publications
(264 citation statements)
references
References 24 publications
8
246
0
10
Order By: Relevance
“…[16][17][18] In addition, both eating disorders and BDD are characterized by obsessional preoccupations and repetitive behaviors (e.g., mirror checking, body measuring). 13,15 Indeed, modifications of the Yale-Brown Obsessive Compulsive Scale (Y-BOCS) are used to assess the severity of both BDD and eating disorders (anorexia nervosa [AN] and binge eating disorder [BED]), [19][20][21] and both disorders have been characterized as obsessivecompulsive spectrum disorders. [22][23][24] In addition, clinical observations suggest that BDD and eating disorders share overvalued and often firmly sustained appearance-related beliefs, as well as a quest to improve one's appearance.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] In addition, both eating disorders and BDD are characterized by obsessional preoccupations and repetitive behaviors (e.g., mirror checking, body measuring). 13,15 Indeed, modifications of the Yale-Brown Obsessive Compulsive Scale (Y-BOCS) are used to assess the severity of both BDD and eating disorders (anorexia nervosa [AN] and binge eating disorder [BED]), [19][20][21] and both disorders have been characterized as obsessivecompulsive spectrum disorders. [22][23][24] In addition, clinical observations suggest that BDD and eating disorders share overvalued and often firmly sustained appearance-related beliefs, as well as a quest to improve one's appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Os autores concluíram pela ausência de evidência de eficácia em longo prazo no uso de antidepressivos para o controle do TCAP 54,55 . O topiramato mostra-se eficaz na redução de episódios de compulsão alimentar em diversos estudos [56][57][58] . Zilberstein et al documentaram a eficácia de topiramato em pacientes apresentando compulsão alimentar após colocação de banda gástrica (LAGB) 59 .…”
Section: Compulsão Alimentar E Cirurgia Bariátricaunclassified
“…21 It is also efficacious in the treatment of binge-eating disorder associated with obesity. 22 Clinical trials of TPM in obese patients demonstrated that TPM was significantly more efficacious than placebo. 5,6,22 Current investigation of TPM as a potential new therapy for obesity is underway.…”
Section: Discussionmentioning
confidence: 99%
“…22 Clinical trials of TPM in obese patients demonstrated that TPM was significantly more efficacious than placebo. 5,6,22 Current investigation of TPM as a potential new therapy for obesity is underway. 23 Glucose uptake lies at the center when dealing with energy expenditure and glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%